Social Criticism In Seno Gumira Ajidarma’s Short Stories And Its Implication For Literary Learning - Falakhi, Miftah; Khamyod, Thitinart; Jlassi, Mohamed (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to describe social criticism in the short stories “Telinga,” “Maria,” and “Kepala di Pagar Da Silva” by Seno Gumira Ajidarma and analyze its implication for literary learning using a mimetic approach. Methodology: This study employed a qualitative descriptive method with a mimetic approach. Data were obtained from three selected short stories in the Trilogi Insiden by Seno Gumira Ajidarma. Data collection used documentation techniques, and analysis was conducted by identifying intrinsic elements and correlating them with social issues outside the texts. Main Findings: The study found that the stories reflect strong elements of social criticism, particularly issues of violence, human rights violations, and political oppression. These criticisms are conveyed through characters, settings, conflicts, and narrative styles. Each story represents different victim perspectives in a conflict zone, making it relevant for fostering critical thinking in literary education. Novelty/Originality of this study: This study highlights how literary texts can serve as a medium of social criticism and suggests how they can be implemented in literary learning to develop students’ social awareness and critical analysis skills. The novelty lies in its integration of mimetic theory with practical implications in education.